Patterns and determinants of Indonesian accounting students’ career choice - Etty Indriani; Nugroho Wisnu Murti (Universitas Hayam Wuruk Perbanas, 2018)
This study investigates the patterns and determinants of accounting students’ career choice by comparing five types of accountant careers to non-accountant career. This study collected data from 216 Indonesian accounting students through Qualtrics online survey and used multinomial and logistic regressions for data analysis. This study found that government accountant was the most dominant career choice among the students (37.04%). Salary consideration as a biggest determination factor (RRR: 2.6231) followed by professional recognition, family & colleagues’ encouragement and education. Meanwhile, career in appraisal was the smallest choice (4.63%), however this need more attention because information about appraisal from the college had positive predictor (OR: 1.0242), while professional recognition was the second biggest predictor to choose appraisal (RRR: 12.8063) after public accountant (RRR: 33.1328). This result could be the colleges’ reminder to provide accounting curriculum not only generally, but also specifically to provide information on different accounting career that fits both the demand of workforce and the students’ preference. College needs to pay attention in students’ preference because this result found that student always had positive expectation in all types of accountant career based on professional recognition, even better than salary expectation which is positive only in government accountant.